Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s12665-009-0353-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of selected riparian herbs in reducing soil erosion and nutrient loss under simulated rainfall

Abstract: The native riparian herbs such as Leonotis nepetaefolia (L.) R. Br., Cassia tora L., Ageratum conyzoides L., Parthenium hysterophorus L. and Sida acuta burm f., dominant on the bank of River Damodar in Eastern Jharia Area, Dhanbad (India), were selected to assess experimentally their quantitative role in conserving the soil and reducing water runoff and nutrient (N and P) losses. A total of 42.5 mm simulated rainfall were applied at 30 cm h -1 rain intensity on both vegetated and bare plots. The collected runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Riparian vegetation, which is the last barrier for the highland runoff and sediment transport to the river in the basin, plays an important role in intercepting, filtering and depositing the soil particles of surface runoff, stabilizing river banks and preventing river bank erosion and collapse by enhancing infiltration, reducing runoff and flow velocity and improving soil corrosion resistance [7,12]. Previous studies have explored the relationship between riparian vegetation and soil and water conservation specifically focusing on vegetation type, coverage, root system [13][14][15], structural characteristics of vegetation [16,17], distribution and arrangement of vegetation [18] and the coupled models of vegetation pattern and the soil erosion process [19]. For example, Srivastava et al [13] and Xia et al [14] analyzed the effects of riparian vegetation on slope erosion by creating field simulated rainfall or performing runoff scouring experiments to determine the effect of presence or absence of vegetation on slope erosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riparian vegetation, which is the last barrier for the highland runoff and sediment transport to the river in the basin, plays an important role in intercepting, filtering and depositing the soil particles of surface runoff, stabilizing river banks and preventing river bank erosion and collapse by enhancing infiltration, reducing runoff and flow velocity and improving soil corrosion resistance [7,12]. Previous studies have explored the relationship between riparian vegetation and soil and water conservation specifically focusing on vegetation type, coverage, root system [13][14][15], structural characteristics of vegetation [16,17], distribution and arrangement of vegetation [18] and the coupled models of vegetation pattern and the soil erosion process [19]. For example, Srivastava et al [13] and Xia et al [14] analyzed the effects of riparian vegetation on slope erosion by creating field simulated rainfall or performing runoff scouring experiments to determine the effect of presence or absence of vegetation on slope erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the relationship between riparian vegetation and soil and water conservation specifically focusing on vegetation type, coverage, root system [13][14][15], structural characteristics of vegetation [16,17], distribution and arrangement of vegetation [18] and the coupled models of vegetation pattern and the soil erosion process [19]. For example, Srivastava et al [13] and Xia et al [14] analyzed the effects of riparian vegetation on slope erosion by creating field simulated rainfall or performing runoff scouring experiments to determine the effect of presence or absence of vegetation on slope erosion. However, the interaction and relative contribution between the vegetation coverage and slope gradient were not taken into consideration in these studies when investigating the inhibiting effects of riparian vegetation on slope runoff and sediment yield; meanwhile the quantitative evaluation of the relevant factors in soil erosion process should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…For example, A. conyzoides planted as a riparian wetland herb on the banks of the Rihand River in Renukoot reduced erosion of organic carbon and cationic nutrients and helps in soil conservation (Kumar et al, 1996). A. conyzoides also maintains the texture and fertility of soil along rivers through reducing soil erosion (Srivastava et al, 2009). A. conyzoides was even reported to be used successfully as a substrate for oyster mushroom cultivation that helps to increase its protein content and production time (Nirmalendu and Mina, 2007).…”
Section: Nematicidal Effects and Miscellaneous Uses Of A Conyzoidesmentioning
confidence: 99%
“…Ageratum conyzoides planted as a riparian wetland herb on the banks of the Rihand River in Renukoot plays a positive role in reducing erosion of organic carbon and cationic nutrients and helps in soil conservation (Kumar et al, 1996). Recently, it has been observed that A. conyzoides helps in maintaining the texture and fertility of soil along the River Damodar riparian zone in Bhowra, as soil erosion was minimized to a great extent following its planting compared with bare areas (Srivastava et al, 2009).…”
Section: Herbicidal Valuementioning
confidence: 99%